The effect of side friction on road capacity (case study: teuku umar road and imam bonjol road) - Hasyim, Abdurrachman Yusuf; Karami, Muhammad; Ofrial, Siti Anugrah Mulya Putri (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
AbstractSide friction are side-road activities that have a significant effect. The high level of roadside activity affects the capacity and performance of roads in an urban area, with the cause of the growing and developing population activity every year. This study uses a method that is guided by the Guidelines for Indonesia's Road Capacity (PKJI 2014).  In this study, the value of side friction on Teuku Umar's road (Advent Hospital – Koga Market) was 567 skr / hour (medium class), while on Imam Bonjol's road (Langkapura) it was 158skr / hour (low class). For the Teuku Umar's road there was a decrease in capacity by 4%, while on the Imam Bonjol's road there was a decrease in capacity by 1%. The cause of congestion on Teuku Umar's road is due to vehicles turning around and vehicles coming in and out of the road, while on Imam Bonjol's road it is due to vehicles going in and out of the road. So that the alternative solution to overcome traffic jams on Teuku Umar's road (Koga market - RS Advent) is to curb motorists who stop carelessly on the road, and set the traffic signs that prohibited from stopping on each side of the road, while on Imam Bonjol's road (langkapura– kemiling) it is necessary to monitor vehicles entering / exiting the alley, because it has the potential to cause long traffic jams. Keywords : Side friction, Guidelines for Indonesia's Road Capacity, Traffic.